Africana-Christian Comparative Theology: Challenges, Opportunities and Perspectives - Hounguevou, Barnabé (Concilium, 2025)
African theology has been profoundly shaped by two dominant currents: inculturation theology and liberation theology. While these frameworks continue to be foundational, comparative theology offers a valuable opportunity to deepen theological engagement with Africana religious traditions. The Africana religious landscape challenges comparative theology to move beyond traditional text-based methods. Given the significance of oral theology and rituals in Africana religions, comparative theology needs to incorporate ethnographic approaches. This exchange is mutually enriching, as comparative theology can offer fresh insights into religious hybridity and the issue of healing which are key concerns in African theology.